Study on the mechanism of the effect of graphene on the rheological properties of rubber-modified asphalt based on size effect. (18th January 2023) - Gao, Yingli; Xie, Yutong; Liao, Meijie; Li, Yuelin; Zhu, Juncai; Tian, Weiwei
Highlights: The improvement of the rheological properties of asphalt by graphene was studied. Using multiple-scale experiments combined with molecular dynamics simulation. The focus is on the size effect of graphene on the modification efficiency. Abstract: The use of waste rubber powder modified asphalt (RA) in road engineering can lead to environmental and economic benefits. However, there are still some concerns over the performance of the pavement with RA, especially the rheological properties under heavy traffic conditions. This paper aims to investigate the improvement effects of graphene on the rheological properties of RA using multiple-scale experimental characterizations combined with molecular dynamics simulation. Special attention was paid to the influence of geometric characteristics of graphene on the modification efficiency. The experimental findings demonstrated that the physical blending of graphene and RA could enhance viscoelasticity, persistent deformation, and mobility resistance of modified asphalt, while its low-temperature performances were marginally improved with the graphene. Graphene with a single layer or a few layers was more efficient in enhancing the high-temperature deformation and rutting resistance and microstructures of RA than that with multiple layers. The molecular dynamics simulation results showed that graphene could improve the shear viscosity of the modified asphalt and inhibit the diffusion of asphalt components, and the effect on the low-temperature performance is related to the size effect. Moreover, the size of graphene particles could strongly influence the performances of the modified asphalt. Specifically, increasing the graphene size decreased the shear viscosity, free volume fraction, and glass transition temperature, indicating the improved deformation resistance. The change in the number of graphene layers was more effective in altering the modification effect of small-sized graphene compared to large-sized graphene. This research can offer a theoretical guideline for optimizing the use of graphene in modified asphalt.